In silico analysis of angiotensin-converting enzyme inhibitory compounds obtained from soybean [Glycine max (L.) Merr.] - Ramlal, Ayyagari; Bhat, Isha; Nautiyal, Aparna; Baweja, Pooja; Mehta, Sahil; Kumar, Vikash; Tripathi, Shikha; Mahto, Rohit Kumar; Saini, Manisha; Mallikarjuna, Bingi Pujari; Saluja, Shukla; Lal, S. K.; et al. (Frontiers in Physiology, 2023)
Cardiovascular diseases (CVD) are one of the major reasons for deaths globally. The renin-angiotensin-aldosterone system (RAAS) regulates body hypertension and fluid balance which cause CVD. Angiotensin-converting enzyme I (ACE I) is the central Zn-metallopeptidase component of the RAAS playing a crucial role in maintaining homeostasis of the cardiovascular system. The available drugs to treat CVD have many side effects, thus there is a need to explore phytocompounds and peptides to be utilized as alternative therapies. Soybean is a unique legume cum oilseed crop with an enriched source of proteins. Soybean extracts serve as a primary ingredient in many drug formulations against diabetes, obesity, and spinal cord-related disorders. soy proteins and their products act against ACE I which may provide new scope for the identification of potential scaffolds that can help in the design of safer and natural cardiovascular therapies. In this study, the molecular basis for selective inhibition of 34 soy phytomolecules (especially of beta-sitosterol, soyasaponin I, soyasaponin II, soyasaponin II methyl ester, dehydrosoyasaponin I, and phytic acid) was evaluated using in silico molecular docking approaches and dynamic simulations. Our results indicate that amongst the compounds, beta-sitosterol exhibited potential inhibitory action against ACE I.